LCZ696 Attenuated Doxorubicin-Induced Chronic Cardiomyopathy Through the TLR2-MyD88 Complex Formation - Ye, Shiju; Su, Lan; Shan, Peiren; Ye, Bozhi; Wu, Shengjie; Liang, Guang; Huang, Weijian (Frontiers in Cell and Developmental Biology, 2021)
Background and Purpose: The profibrotic and proinflammatory effects induced by doxorubicin (DOX) are key processes in the development of serious heart damage. Lack of effective drugs and the unclear mechanisms of its side effects limit the clinical treatment of DOX-induced cardiac injury. This study aimed to explore the protective role of LCZ696 and the potential mechanism of Toll-like receptor 2 (TLR2) in doxorubicin-induced cardiac failure. Experimental Approach: DOX (5mg/kg/week, 3times) was used to establish a chronic cardiomyopathy mouse model. Heart function tests, pathology examinations and molecular biology analyses were used to explore the effects of LCZ696 and TLR2 deficiency in vivo and in vitro. Computational docking was applied to predict the key residues for protein-ligand interaction. Key Results: The EF% declined, and the LVIDd, pro-fibrosis marker levels and NF-κB related inflammatory response increased in the chronic cardiomyopathy group induced by DOX. LCZ696 treatment and TLR2 deficiency reversed these heart damage in vivo. In H9C2 cells, pretreatment with LCZ696 and TLR2 knockdown suppressed the DOX-induced high expression of profibrotic and proinflammatory markers. Moreover, DOX notably increased the TLR2-MyD88 interaction in vivo and in vitro, which was inhibited by LCZ696. Finally, we demonstrated the direct interaction between DOX and TLR2 via hydrogen bonds on Pro-681 and Glu-727 and Pro-681 and Ser-704 may be the key residues by which LCZ696 affects the interaction between DOX and TLR2. Conclusion and Implications: LCZ696 prevents DOX-induced cardiac dilation failure, fibrosis and inflammation by reducing the formation of TLR2-MyD88 complexes. LZC696 may be a potential effective drug to treat DOX-induced heart failure.